ANALISIS PENGARUH TINGKAT NISBAH BAGI HASIL, PENERAPAN AKAD DAN PROMOSI TERHADAP MINAT MENABUNG PADA KOPERASI AL-IQTISHOD UNISMA - Isnaini Isnaini; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study aims to determine the effect of the profit-sharing ratio, the application of contracts and promotions on interest in saving at the Al Iqtishod cooperative, Islamic University of Malang. This study uses quantitative data with primary data. This research uses purposive sampling method. The sample used in this study was 50 respondents. The data analysis method used in this research is multiple regression analysis. The results of this study simultaneously show that the profit-sharing ratio, contract application, and promotion variables simultaneously have a significant effect on saving interest. Partially, the variable profit sharing ratio partially has a significant positive effect on saving interest. The variable of the application of the contract partially has a significant positive effect on the interest in saving. The promotion variable partially has a significant positive effect on saving interest. Keywords: Profit Sharing Ratio, Implementation of Contracts, Promotion, Interest in Savings